THE UNLUCKY NUMBER IN CULTURAL PERSPECTIVE OF JAPANESE SOCIETY - Suhartini Suhartini (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
This article tries to reveal the cultural perspective of Japanese society on unlucky number, that is 4. Comprehending this phenomenon is needed by those who intend to cooperate or make relation with the Japanese in order to get better understanding. Library research and interview with native speakers of Japanese and Chinese are conducted in this research. The result shows that 4 is considered an unlucky number because linguistics link in the form of homophone or similarity of sound between the Japanese numeralia’s pronounciation of absorbed from Chinese, that is shi [ɕi] meaning ‘number 4’, and a Japanese root verb’s pronounciation shi [ɕi] of shinu [ɕinɯ] meaning ‘death’. Although today the number is often used in public, some Japanese still avoid it directly or indirectly. Direct avoidance is done by not using 4 or refusing anything related to the number. Indirect avoidance is done by using numeralia yon which is the synonym of shi, both of which mean 4.